UTILIZATION OF BOOSTER CIRCUIT JOULE THIEF FOR GARDEN LIGHTING SOURCE OF VOLTAGE FROM THE SUN - Ricki Ananda; Muhammad Amin (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2021)
Abstract: Garden lighting from a sun source utilizes a series of joule thieves so that the lighting of the garden lights at night is bright. This research method uses a quantitative method because it must be tested on each module so that it finds that there are three types of module systems to be combined, the booster or joule electronic thief module, the supply media solar module circuit, and finally, the control system with the Arduino nano board. The solar module used is a 1-watt solar module with 1n4004 diodes, which will convert the heat of sunlight into voltage. The voltage will be sent via the IC TP4056 input, the output from the IC TP4056 will charge the 18650 battery, which aims to ignite the booster circuit on the 12 W lamp, or the 3.7VDC input from the 18650 battery capable of turning on the 12W/220VAC led light. While the controller is connected to the LDR sensor and relay when the user makes the command, LDR > 800 of the provisions, the relay position from NC becomes open, or during the day, the relay will be in the NC position and turn off the 12W light in the booster circuit, while at night the relay will remain in the no position, so that it will connect the booster circuit voltage and turn on the 12W lamp (LDR < 800).Keywords: booster circuit; campus park lighting; solar panels  Abstrak: Penerangan taman dari sumber matahari memanfaatkan rangkaian joule thief agar penerangan lampu taman pada malam hari terang. Metode penelitian ini menggunakan metode kuantitatif dikarenakan harus diuji coba pada tiap modul, sehingga mendapati ada tiga jenis sistem modul yang akan digabungkan, modul elektronika rangkaian booster atau joule thief, rangkaian modul surya media pensuplly, dan terakhir sistem controller dengan board arduino nano. Modul surya yang digunakan modul surya 1 watt dengan dioda 1n4004, akan mengubah panas cahaya matahari menjadi tegangan . Tegangan akan dikirimkan melalui input IC TP4056, output dari IC TP4056 akan mengisi baterai 18650 yang bertujuan sebagai penyala rangkaian booster pada lampu 12 W, atau input 3.7VDC dari baterai 18650 mampu menyalakan lampu led 12W/220VAC. Sementara controller terhubung kesensor ldr dan relay, ketika perintah yang dibuat oleh user, ldr > 800 dari ketentuan, posisi relay dari nc menjadi open, atau siang hari, relay akan diposisi nc dan mematikan lampu 12W pada rangkaian booster, sementara jika malam hari relay akan diposisi no, sehingga akan menghubungkan tegangan rangkaian booster dan menyalakan lampu 12W (ldr < 800).  Kata kunci : panel surya, penerangan taman, rangkaian booster.